2019
DOI: 10.2147/jpr.s185652
|View full text |Cite
|
Sign up to set email alerts
|

<p>Qualitative evaluation of an interdisciplinary chronic pain intervention: outcomes and barriers and facilitators to ongoing pain management</p>

Abstract: Background Many leaders in the field of chronic pain treatment consider interdisciplinary pain management programs to be the most effective treatments available for chronic pain. As programs are instituted and expanded to address demands for nonpharmacological chronic pain interventions, we need to better understand how patients experience program impacts, as well as the challenges and supports patients encounter in trying to maintain and build on intervention gains. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…Substantially different experiences from multidisciplinary pain treatments have also been found by others. One study showed that the overall impact of an interdisciplinary chronic pain intervention programme could be placed along a spectrum from whole life change to no change [22], whereas another study used the labels ‘overall life changes’ and ‘stagnation’ [27] to describe different experiences of a multimodal cognitive chronic pain treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Substantially different experiences from multidisciplinary pain treatments have also been found by others. One study showed that the overall impact of an interdisciplinary chronic pain intervention programme could be placed along a spectrum from whole life change to no change [22], whereas another study used the labels ‘overall life changes’ and ‘stagnation’ [27] to describe different experiences of a multimodal cognitive chronic pain treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A strength of the study is the novelty in the exploration of experiences of persons attending outpatient individual multidisciplinary pain treatment that was not part of inpatient, group based or time-limited programmes, as in e.g., [22, 29, 30]; however, there are some noteworthy limitations. The aim was to obtain data that represented the variations in patients’ experiences in Norwegian pain centres in order to answer the research question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research suggests that patients typically benefit from interdisciplinary approaches to pain management, including lifestyle modification, movement therapies, and mind-body based treatments. 32 Patients' behavioral treatment preferences did not always exactly mirror doctor recommendations, and those who had received behavioral recommendations typically noted interest in several approaches, suggesting that there may be room for discussion of multiple approaches to pain management. Discussing these multiple approaches may ultimately increase receipt, as patients cite having a wide array of treatment options as a facilitator to using behavioral treatments for chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Limited evidence exists exploring perceptions of which aspects of a pain management program are valuable and impactful, which could guide the implementation of service delivery and program redesign. Qualitative studies, which can achieve this purpose, have previously concentrated on other aspects including, but not limited to: patient values in the years following a high-intensity program [ 16 ], the patient’s perceived barriers and facilitators to self-management [ 17 , 18 , 19 ], the patient’s perceptions of themselves [ 20 ] and of changes that have occurred after a program [ 16 , 21 ], broader perceptions of pain treatments and life [ 22 ], navigating chronic pain healthcare systems [ 23 , 24 ], successful strategies used outside of a pain management program [ 25 ], perspectives on opioids [ 26 , 27 ], and patient’s expectations about a program [ 28 ]. Understanding more about participant perceptions could improve the acceptance of active evidence-based therapies like pain management programs [ 29 ].…”
Section: Introductionmentioning
confidence: 99%